Influence of border effect on selection of cassava genotypes - Bueno, Álvaro (Pesquisa Agropecuaria Brasileira, 2014)
With the objective to determine the response of different gonotypes of cassava (Manihat esculenta Crantz) to cultivation in plots with complete border rows and without external and internal border rows, four experiments were carried out at the experimental site of the Centro Nacional de Pesquisa de Mandioca e Fruticultura (CNPMF) in Cruz das Almas, BA, Brazil. Fresh root and above ground plant yields were measured in the different plots. Results show that fresh root and upper part mean yields wore overestimated in plots without external border rows, but they were not significantly altered in plots without internal border rows. The accuracy of the experiments was nor sufficient for an exact identification of the internal border effects. However, in advanced yield trials these border rows are necessary.